Islamic Perspective on the Tradition of ‘Mandi Safar’ in the Long Tomb of Pengujan Village - Aqmal, Romi (Advances in Humanities and Contemporary Studies, 2022)
Abstract: Indonesia is an archipelago country with the community diversities spread out from Sabang to Merauke. Various customs and cultures that are always upheld by the people of an area including the values contained therein. Likewise, the tradition of ‘Mandi Safar’ in the long tomb by the people of hamlet I, Pengujan Village. This tradition is performed based on the belief of the local community who think that this tradition needs to be carried out in order to maintain the security and peace of the local area as well as the form of respect for the ancestral spirits. The purpose of this study was to explore the Islamic perspective on the tradition of ‘Mandi Safar’ done by the people of Hamlet I of Pengujan Village by using a descriptive qualitative approach. The data were collected by directly interviewing the informants that were from the local people of Hamlet 1 Pengujan Village, Bintan Regency, Riau Islands Province, Indonesia.